(untitled) - Obeidi, Mahdi (Hoboken, N.J., 2004)
In The Bomb in My Garden, Dr. Obeidi reveals how he circumvented the international safeguards specifically intended to bar developing nations from obtaining the knowledge and materials needed to build nuclear weapons. He recounts his many "shopping trips" abroad, during which he inveigled, bribed, and cajoled scientists and engineers at companies throughout the United States and Europe into assisting him. And he details the complex system of front companies and financial institutions he used to pull it all off.
Keywords: Nuclear weapons,Nuclear physicists,Nuclear nonproliferation,Vũ khí hạt nhân,Vật lý hạt nhân,Hạt nhân không phổ biến; Iraq,Iraq,Iraq,I rắc,I rắc,I rắc